Diagnosis Of Malnutrition In Children Using The Dempster Shafer Method - Br Sbt, Sri Devi; Fauzi, Achmad; Syahputra, Siswan (Devitara Innovations, 2024)
Malnutrition is a serious problem that can interfere with a child's physical growth, cognitive development, and general health. This study aims to develop a web-based expert system that is able to diagnose malnutrition in children using the Dempster Shafer method.Conventional methods in diagnosis often face challenges such as uncertainty and subjectivity, so a more accurate and efficient approach is needed. The Dempster Shafer method was chosen because of its ability to overcome uncertainty by combining various sources of information to produce a more precise diagnosis. This research was conducted at the Djoelham Regional General Hospital, Binjai City, with a focus on children aged 0-12 years. The expert system, which is designed using the PHP programming language and MySQL database, is expected to replace the role of an expert in providing initial diagnosis, making it easier for parents and health workers to take quick and appropriate actions. The results of this study show that the expert system developed is able to provide malnutrition diagnosis to children with good accuracy, so that it can be used as a tool in handling malnutrition problems more effectively.